Pengembangan Pariwisata Berkelanjutan melalui Pendekatan Manajemen Strategis - Mangihut Siregar; Baktiawan Nusanto; Taufik Hidayat; Ely Mulyadi (Empat Sembilan Publisher, 2025)
Sustainable tourism development is a strategic issue in regional development because it is directly related to economic growth, environmental conservation, and social welfare of the community. However, tourism management in various regions still faces challenges in the form of limited strategic planning, weak coordination between stakeholders, and the lack of optimal integration of sustainability principles in destination management policies and practices. This research aims to analyze the development of sustainable tourism through a strategic management approach as the basis for the formulation of a long-term oriented tourism management strategy. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, field observations, and documentation studies on tourism planning policies and documents. The data analysis technique was carried out using SWOT analysis, PESTEL, and stakeholder analysis to identify internal and external conditions as well as the role of actors in tourism development. The results of the study show that the implementation of strategic management is able to comprehensively identify the potential and challenges of tourism development. Internal factors in the form of local resources and institutional support, as well as external factors such as policies, social conditions, and the environment, play a significant role in determining the direction of sustainable tourism strategies. In addition, the active involvement of stakeholders is key in maintaining a balance between economic, social, and environmental interests. This study concludes that the strategic management approach is an effective framework in supporting the development of sustainable tourism. The implications of this study emphasize the importance of collaborative and adaptive strategic planning to realize competitive and sustainable tourism management